Identifying business opportunities for sustainable development: Longitudinal and experimental evidence contributing to the field of sustainable entrepreneurship - Fokko J. Eller; Michael M. Gielnik; Hendrik Wimmer; Corinna Thölke; Sara Holzapfel; Silke Tegtmeier; Jantje Halberstadt (Business Strategy and the Environment, 2020)
Which factors facilitate the identification of business opportunities for sustainable development? To answer this question, we develop a process model of sustainable opportunity identification. We argue that sustainable opportunity identification is a process with transitions from problem to solution identification and from solution to sustainable opportunity identification. Moreover, the transitions are facilitated by two factors—awareness of adverse consequences and entrepreneurial attitude—providing motivation and direction in the process. We tested our model in a field study (N~=~107) and two experiments (N~=~53 and N~=~69). Our findings show that awareness of adverse consequences and entrepreneurial attitude influence the process of sustainable opportunity identification, explaining under which conditions people are more likely to identify business opportunities for sustainable development. Our study thus contributes to the field of sustainable entrepreneurship.
Keywords: 330; adverse consequences; awareness; entrepreneurial attitude; motivation; opportunity identification; sustainability